Спутницы Пушкина: по кн. В. Вересаева "Спутники Пушкина" / авт. предисл. В. Коровин - Коровин В. (Профиздат, 1999)
Экземпляры: (20200722) / Инвентарный номер: 35785 / Цена: 30.00 / Сис.шифр: 83.3(2Рос=Рус)1 / Авт.знак: С 74 / ББК: 83.3(2Рос=Рус)1